The effectiveness of manual therapy in the treatment of temporomandibular disorders (TMD): a review of the literature - Santos, Lúcia de Fátima da Silva (2016)
Introduction: Temporomandibular disorder (TMD) is a subclassification of musculoskeletal dysfunctions and have unknown etiology. Its most common symptoms are orofacial pain and decreased joint mobility of the mouth, sensations that reduce the quality of life of its bearer. Physical therapy appears as an important therapeutic method, and among the methods commonly used, exist the manual therapy. Objective: To conduct a literature review on the effectiveness of manual therapeutic approaches in the treatment of TMD. Materials and methods: We conducted a search in the electronic databases of data Lilacs, SciELO, Medline, and Pubmed gathering clinical trials from 2004 to 2014 which documented manual therapeutic conducts, isolated or associated, used for treating TMD in adults. Results: Eleven articles referring to the intervention of manual therapy in TMD were reviewed, of which nine are Brazilian and two are international. The studies showed effectiveness of manual therapy in relieving painful symptoms, improvement of the pattern of contraction of the masticatory musculature, and restoration of joint mobility through the methods used in the treatment and reported that the significance of the results was obtained from the association between manual techniques and others therapies, such as electrophysical resources and drugs. Conclusion: Based on the study, one can observe that manual therapy presents satisfactory results in treating patients with TMD and that the combination of manual therapy with other therapeutic resources enhances the effects obtained in the treatment of these patients with more significant results.